FORMULASI GLISEROL DAN CMC DALAM PEMBUATAN BIODEGRADABLE FILM BERBASIS SELULOSA DAUN NANAS (Ananas comosus) FORMULATION OF GLYCEROL AND CMC IN MAKING BIODEGRADABLE FILM PINEAPPLE LEAF BASED (Ananas comosus) - Zulferiyenni Zulferiyenni; Maulida Melvina Putri; Suharyono Suharyono; Fibra Nurainy (Jurusan Teknologi Hasil Pertanian, 2023)
Pineapple leaves contain 69.5-71.5% cellulose, which can be used as raw material to make biodegradable films. This study aimed to obtain the best formulation of glycerol and CMC for biodegradable films of pineapple leaves. This research used the triplo method to collect data three times in one sample. Samples are selected based on the best visual appearance and indicated by the few flocs in the sample. The treatment was composed of 6 formulations which were formulations of glycerol and CMC, namely P1 (0%:1%), P2 (0,5%:1,5%), P3 (1%:2%), P4 (1,5%:2,5%), P5 (2%:3%), P6 (2,5%:0%). The data on tensile strength, percent elongation, water vapour permeability, thickness, testing biodegradability and room temperature resistance is presented in pictures and will be discussed descriptively. Formulation of glycerol 1,5% and CMC 2,5% produces the best characteristics of biodegradable films with a tensile strength value of 113,52 MPa, a percent elongation value of 12,71%, and a thickness value of 0,18 mm. Biodegradable film pineapple leaves have a water vapour permeability value of 24,03 (g/m2/hour), biodegradability for 5 weeks and resistance to room temperature for 5 weeks without being overgrown by fungi.